PERANAN MEDIA SOSIAL PADA GERAKAN 5000 DONASI BUKU DALAM UPAYA MEMBANGUN BUDAYA LITERASI : TAHAP 8 - Vidila Rosalina (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
The culture of a nation's people has a very close relationship to the quality of a nation's human resources. The high interest in one's literacy affects the insight, mentality, and behavior of individual humans. The Indonesian nation is a nation with a low level of literacy even though it has been 78 years since Indonesia became an independent country. When literacy culture becomes a culture in Indonesia, it is not impossible that our nation will become a more advanced nation. There are many factors why Indonesian literacy has a low percentage. This problem must immediately receive serious attention not only from the government but from all of us. How can the discourse on reading interest be carried out for all levels of society when we still have a limited number of literature books read? So the 8th stage of the 5000 book donation movement is to utilize social media in disseminating the donation movement so that we can collect and donate as many books as possible as an effort to build a literacy culture and literacy spirit in Indonesia and in Banten in particular.